Author Correction: Preschool children and chimpanzees incur costs to watch punishment of antisocial others. (April 2018) - Mendes, Natacha; Steinbeis, Nikolaus; Bueno-Guerra, Nereida; Call, Josep; Singer, Tania
In the version of this Article originally published, in Fig. 2c the hatching indicating antisocial behaviour was on the wrong data bars. This has now been corrected in the Article.